Comparative assessment of endocrine disrupting compounds removal in heterotrophic and enriched nitrifying biomass. (February 2019) - Kassotaki, Elissavet; Pijuan, Maite; Rodriguez-Roda, Ignasi; Buttiglieri, Gianluigi
Abstract: Despite the number of studies that have investigated the fate of endocrine disrupting compounds (EDCs), to date results are still contradictory and more research is required to evaluate the contribution of the microbial communities present in different engineered treatment systems. Thus, autotrophic and heterotrophic types of biomass were here compared in terms of efficiency in the removal of estrone (E1), 17β-estradiol (E2), estriol (E3), 17α-ethynilestradiol (EE2) and bisphenol A (BPA). Experiments were performed with enriched nitrifying activated sludge (NAS) and enriched ammonia oxidizing bacteria (AOB) sludge cultivated at lab-scale, as well as with conventional activated sludge (CAS) from a full-scale wastewater treatment plant. Both enriched NAS and AOB demonstrated a negligible degrading capacity. In both cases, the studied EDCs exhibited low removals (<14%) and showed no correlation with the increasing nitrification rates contradicting some of the hypothesis present in literature. Contrariwise, the biodegradation capabilities of the heterotrophic fraction of CAS were highlighted. E2 and E3 were removed by up to 100% and 78%, respectively. E1 was found to be the main transformation product of E2 (almost quantitative oxidation) and it was also highly eliminated. Finally, EE2 and BPA were more persistent biologically with removals ranging from 10% to 39%. For these two compounds similar removals were obtained during experiments with heat-inactivated biomass suggesting that sorption could be a relevant route of elimination. Graphical abstract: Highlights: Nitrifiers showed poor degrading capacity in the removal of E1, E2, E3, EE2 and BPA. No correlation between nitrification and E1, E2, E3, EE2 and BPA removal was detected. E2 and E3 were highly removed by heterotrophs, up to 100% and 78% respectively. High removal can also be stated for E1, being the main transformation product of E2. Sorption was evaluated resulting potentially significant for EE2 and BPA.